2020
DOI: 10.22336/rjo.2020.46
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of subfoveal choroidal thickness after panretinal laser photocoagulation in diabetic retinopathy using swept-source optical coherence tomography

Abstract: Purpose: To describe the central three-dimensional (3D) thickness profile of the macula (CMT) and the subfoveal choroidal region (SFCT) in diabetic retinopathy (DR) following panretinal laser photocoagulation (PRP) using swept-source optical coherence tomography (SS-OCT). Methods: A prospective observational study including 17 eyes with proliferative DR (PDR) and 27 eyes with severe nonproliferative DR (sNPDR)] for whom PRP was done. All subjects received SS-OCT imaging before and 3 months after PRP (POM#3). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…A series of studies have shown a significant decrease in subfoveal choroidal thickness after PRP using enhanceddepth OCT [9,[21][22][23]. Our results were consistent with those of previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…A series of studies have shown a significant decrease in subfoveal choroidal thickness after PRP using enhanceddepth OCT [9,[21][22][23]. Our results were consistent with those of previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Before the introduction of intravitreal anti-VEGF agents, laser photocoagulation was the standard of care for DME treatment. It was introduced to the field of ophthalmology over 25 years ago [ 29 , 41 ]. In 1985, in the Early Treatment Diabetic Retinopathy Study (ETDRS), a multicenter randomized trial exploring the benefits of laser therapy for retinopathy, it was demonstrated that photocoagulation could halve the risk of moderate visual loss over three years from 24% to 12% compared to deferred treatment [ 42 ].…”
Section: Current Therapeuticsmentioning
confidence: 99%
“…The SFCT increases 1 week after PRP (55), since damage to the peripheral choriocapillaris causes peripheral choroidal blood flow to decrease and redistributes the blood flowing from the peripheral to foveal Centralia (58). However, SFCT also decreases at one (55,56) and 3 months (55,59) after PRP because of the reduction in total choroidal capillary blood flow. Although, we have excluded patients who received focal treatment for DR in the last 3 months, a potential bias may remain especially in sNPDR and PDR.…”
Section: Wmd (95% Ci) Imentioning
confidence: 99%